Displacement Patterns of Blunt Rib Fractures and Their Relationship to Thoracic Coinjuries: Minimal Displacements Count. Issue 3 (March 2016) - Bugaev, Nikolay; Breeze, Janis L.; Alhazmi, Majid; Anbari, Hassan S.; Arabian, Sandra S.; Rabinovici, Reuven
Displacement patterns of rib fractures (RF) and their association with thoracic coinjuries and outcomes are unknown. This is a retrospective review of adult patients with blunt closed RF who underwent chest CT at a Level I trauma center (2007–2012). Displacement patterns of RF were compared among the three-dimensional planes using CT images. An analysis of receiver operating characteristic (ROC) curves was performed to identify displacements in each plane most strongly associated with chest coinjuries. Univariate analysis was used to find association of displaced RF with hospital course and outcome. There were 1127 RF (245 patients, most in ribs 3–9, 45 per cent displaced). Axial displacement was the most common, with odds ratios 7.20 and 2.13 compared with cranio-caudal, and impaction-separation (along rib axis) movement, respectively. Axial displacement thresholds performed well with hemothorax (2.8 mm, ROC = 0.74), pneumothorax (2.6 mm, ROC = 0.70), hemopneumothorax (3.1 mm, ROC = 0.77), flail chest (3.4 mm, ROC = 0.80), and chest tube placement (2.8 mm, ROC = 0.75). RF displacement was associated with increased days on mechanical ventilation and hospital length of stay. In conclusion, even minimal RF displacement is associated with increased risk of chest coinjuries and chest tube placement, and displacements correlated with increased days on mechanical ventilation and hospital length of stay. Future studies are required to investigate these associations, especially in relationship to the indications for rib plating.